2021
DOI: 10.5582/irdr.2020.03143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation and genetic analysis of familial rare disease genodermatosis xeroderma pigmentosum

Abstract: Xeroderma pigmentosum (XP) is a rare autosomal recessive disease characterized by hypersensitivity of the skin to ultraviolet radiation and other carcinogenic agents. This ailment is characterized by increased photosensitivity, skin xerosis, early skin aging, actinic keratosis, erythematous lesions, and hyperpigmentation macules. In this serial case report, we presented four cases with XP from two families in Indonesia. Both families were referred from rural referral health centers, and each family has two aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Moreover, the incidence is genetically determined and increases with consanguinity. 2 The only one case of XP in Indonesia was reported by Yuniati et al 4 They reported a novel pathogenic variant of XPC, c1941T>A that was found in the second family. 4 To date, there has not been any specific XP gene mutation research in Indonesia yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the incidence is genetically determined and increases with consanguinity. 2 The only one case of XP in Indonesia was reported by Yuniati et al 4 They reported a novel pathogenic variant of XPC, c1941T>A that was found in the second family. 4 To date, there has not been any specific XP gene mutation research in Indonesia yet.…”
Section: Discussionmentioning
confidence: 99%
“…2 The only one case of XP in Indonesia was reported by Yuniati et al 4 They reported a novel pathogenic variant of XPC, c1941T>A that was found in the second family. 4 To date, there has not been any specific XP gene mutation research in Indonesia yet. Gene mutation testing and family counseling could help in early detection and determine various clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Actinic keratoses are observed at an early age, and actinic cheilitis is not uncommon. 11,23,39 The anterior parts of the eye (conjunctiva, lens, cornea and eyelids) are particularly susceptible to damaging effects of UVR in patients with XP. 6,40 The posterior parts of the eye are protected by the lens which acts as a barrier to UVR.…”
Section: Aetiopathogenesismentioning
confidence: 99%